Rapid conglutination test for diagnosis of Babesia bovis antibodies - Roberto Madruga, Claudio; Henrique Kessler, Raul; Miguita, Midori (Pesquisa Agropecuaria Brasileira, 1998)
The objective of this work was to develop and evaluate a rapid conglutination test (RCT) for detection of antibodies against Babesia bovis (B. bovis-RCT), with similar performance as the indirect immunofluorescence test. The B. bovis-RCT had a sensitivity of 95.7%, a specificity of 97.6% and the precision of 96.5%, the same parameters for the IFAT being 99.1%, 99.7% and 99.4% respectively. The RCT was able to detect immunoglobulins anti-B. bovis as early as IFAT after bovine challenge with these hemoprotozoans. B. bovis-cross reactions with sera of Babesia bigemina infected cattle were 4%. The RCT prepared with non-parasitized erythrocytes (negative antigen) showed 3.5%, 1.5% and 2.2% of positive reactions with sera of animals infected with B. bovis, B. bigemina and Anaplasma marginale. None of sera from animals in endemic areas had positive reactions with this antigen. Considering these results and the viability of B. bovis-RCT (172 to 245 days, stored at 4ºC), it can be concluded that this serological test can be used for epidemiological studies and the evaluation of control measures against this species of Babesia.